Optimization Of Inclusive Interpretation Insights In The Qur'an Hadith Teacher Group In Kuala Sungai Ambawang Village, Sungai Ambawang Regency, Kubu Raya Regency, West Kalimantan - Udi Yuliarto; Taufik Akbar (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
In the era of disruption, inclusive interpretation becomes a strategic solution to counter radicalism and foster a moderate and contextual understanding of religion. Technological disruption introduces new challenges in education, particularly regarding the dissemination of religious information often lacking context. In Kubu Raya Regency, a region with a heterogeneous society, inclusive interpretation plays a vital role in creating social capital for harmony and tolerance. However, challenges in the competency of Qur'an-Hadith teachers in Sungai Ambawang Kuala Village, such as limited academic background and methodology, hinder the optimization of inclusive interpretation. To address these challenges, a community service program was implemented in three phases: preparation (pre-test), implementation (lectures and discussions), and evaluation (post-test and reflection). This program involved teachers from various schools and madrasas, aiming to enhance their understanding of inclusive interpretation in line with the mandate of KMA Number 183 of 2019. The outcomes are expected to support relevant and moderate Islamic education amidst the challenges of the disruption era.